Depolarizing influences regulate preprotachykinin mRNA in sympathetic neurons. - Roach, A (1987)
We have been studying mechanisms regulating neurotransmitter plasticity in sympathetic neurons. Neurons of the rat superior cervical ganglion (SCG) synthesize multiple putative transmitters, including the peptide substance P (SP). We have now examined steady-state levels of the mRNA encoding preprotachykinin (PPT), the SP precursor. A cloned cDNA probe was used to examine regulation mRNA levels in culture and in vivo. In RNA gel blot experiments, a single band (1.1 kilobases long) was observed in all cases in which an RNA was detected. A low level of PPT mRNA was detected by RNase protection assay in uncultured ganglia, suggesting that the low levels of SP previously observed in the normal ganglion in vivo are synthesized locally. When ganglia were maintained in culture, with consequent denervation, the steady-state level of PPT mRNA increased by 25-fold over the first 24 hr, and the high level was maintained for at least 7 days. RNase protection experiments indicated that the major message in the SCG is the beta-PPT mRNA, encoding both SP and neurokinin A peptide regions. Accumulation of the PPT mRNA in cultured ganglia was sharply inhibited by the depolarizing agent veratridine, and this effect was blocked by tetrodotoxin. Therefore, one form of neuronal plasticity, change in neurotransmitter metabolism, is regulated at least in part by altering steady-state levels of specific mRNA. More generally, extracellular signals may contribute to neuronal plasticity through changes in gene expression.